Anti-transglutaminase IgA antibody measurement in coeliac disease: Method comparison IDS-iSYS vs. Thermo Fisher Phadia. (2nd November 2020) - Sandfeld-Paulsen, Birgitte; Parkner, Tina; Knudsen, Cindy Soendersoe
Abstract: In coeliac disease, the diagnostic work-up is based on a combination of clinical, histopathological and serological evaluation. Among the serological tests, the presence of tissue transglutaminase (tTG) IgA antibodies is the cornerstone owed to a high sensitivity and specificity. Recently, Immunodiagnostic Systems Ltd (IDS) introduced the fully automated chemiluminescent autoimmune assays for use on the IDS-iSYS Multi-Discipline Automated System. In this study, we aimed to compare the performance of the IDS-iSYS assay to the Thermo Fisher Phadia assay and to establish the upper reference limit of tTG IgA in a healthy population from Denmark based on the IDS-iSYS assay. We discovered a total imprecision of CV = 12.2% (2.87 AU/mL) and CV = 10.6% (47.55 AU/mL). Moreover, we compared the performance of IDS-iSYS assay to Thermo Fisher Phadia assay in 236 samples from unselected patients submit for tTG IgA testing and found a concordance of 97% ( p  < .0001). Furthermore, in 150 healthy blood donors, we established the upper reference limit of 3.26 AU/mL (95% CI: 3.10 − 3.90) was identified. Our study validates the performance of the IDS-iSYS tTG IgA assay and demonstrates results in concordance with the established Thermo Fisher Phadia. Furthermore, it provides estimates for the upper reference interval limit of the tTG-IgA.